Case Study : Obsess Cosmetics / Nik Nur Hidayah Ma Hassan - Ma Hassan, Nik Nur Hidayah (2021)
Obsess Cosmetics is a locally developed firm started by Hafizatul Atikah. Before starting the business, Hafizatul Atikah was a well-known makeup artist. The headquarters of Obsess Cosmetics are located in Jerantut, Pahang. They started as a corporation in 2015 and were relatively unknown in Malaysia at the time. They invested RM60000 in the start-up of their company. Obsess cosmetics isn't a brand that pops up out of nowhere in the beauty industry. Obsess Cosmetics has been a part of its users' lives for a long time. Obsess Cosmetics was started in 2016 by a makeup artist with years of expertise. Their headquarters are located in Jerantut, with a monthly rental of RM3000. Only four people work at their headquarters from January to October 2019. It was one of the first local brands to create its own cushion foundation in 2016. Its product line has now grown to include eye and cheek cosmetics. The great aspect is that Obsess Cosmetics is reasonably priced and suitable for both professionals and amateurs.